INVENTARISASI JENIS VEGETASI POHON DI LABORATORIUM ALAM PENDIDIKAN BIOLOGI SEBAGAI RANCANGAN BUKU SAKU PADA MATERI KEANEKARAGAMAN HAYATI - Febblina Daryanes; Sri Wulandari; Yuslim Fauziah; Vina Deswita (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2023)
The types of woody plants in the Nature Laboratory of Biology Education FKIP UNRI have not been completely recorded, besides that the results of observations can be used as a source of learning which is still very rare for teachers to develop pocket books. This study aims to inventory tree vegetation at the Nature Laboratory of Biology Education FKIP UNRI as a pocket book design on biodiversity material. The research was conducted in June-September 2021. This research is survey research and development research. Inventory of tree vegetation types using the roaming method. The development of a pocket book on biodiversity material uses the ADDIE development model. The inventory results show that there are 19 types of tree vegetation in the Biology Education Nature Laboratory, namely Alstonia scholaris. R. Br, Rhodamnia cinereal, Sizygium acuminatissimum, Terminalia catappa. L, Aporasa granularis, Blumeodendron kruzii, Maccaranga gigantean, Endospermum javanicum, Artocarpus elasticus, Ficus carica. L, Artocarpus heterophyllus, Calophyllum inophyllum. L, Vitex pinnata, Switenia macrophylla, Peronema canescens, Symplocos cochinchinensis, Diospyros confertiflora, Schima wallichi. Korth, Cocos nucifera. L. The results of the inventory become a source of pocket book information on biodiversity material.